The adverse effects of interferon‐free regimens in 149 816 chronic hepatitis C treated Egyptian patients. Issue 9 (5th March 2018) - Attia, D.; El Saeed, K.; Elakel, W.; El Baz, T.; Omar, A.; Yosry, A.; Elsayed, M. H.; Said, M.; El Raziky, M.; Anees, M.; Doss, W.; El Shazly, Y.; et al.
Summary: Background: Interferon‐free regimens are associated with high sustained virological response; however, associated adverse effects have yet to be fully reported. Aim: To evaluate the adverse effects associated with the different direct‐acting antiviral drug (DAA) regimens in Egyptian patients. Methods: This multicenter retrospective study included all adverse effects during and after treatment with DAA regimens of 149 816 chronic hepatitis C treated Egyptian patients. Patients received sofosbuvir (SOF)/ribavirin (RBV) (n = 21 835), SOF/simeprevir (n = 24 215) SOF/daclatasvir (DCV) (n = 58 477), SOF/DCV/RBV (n = 45 188) and paritaprevir/ombitasvir/ritonavir/RBV (n = 101). The duration of treatment varied between 12 and 24 weeks. All changes in the treatment regimens, discontinuation, mortality, and serious side effects were reported. Results: Adverse effects developed in 2475 (1.7%) (mean age [54 ± 9], male gender [53%]) patients. Serious side effects developed in 68% of these patients, and SOF/RBV was the most common causing regimen (73%, P  < 0.001). Anaemia and hyperbilirubinemia were the most common side effects (731/149816, 0.5% and 463/149816, 0.3%, respectively) and SOF/RBV (588/21835, 3% and 353/21835, 1.6%, respectively) showed the highest incidence in the treated patients. Hepatocellular carcinoma and mortality were reported in 0.02% and 0.06% of all treated patients, respectively. Patients with liver cirrhosis showed higher incidence of serious side effects (Log rank P  = 0.045) and mortality (Log rank P  = 0.025) than patients without liver cirrhosis. Male gender ( P  = 0.012), lower haemoglobin ( P  < 0.001), platelets ( P  < 0.001) and albumin ( P  = 0.001), higher bilirubin ( P  = 0.002) and cirrhosis ( P  < 0.001) were factors associated with serious side effects development. Conclusion: Adverse effects associated with DAAs are few, anaemia being the most common. SOF/RBV regimen showed the highest rate of side effects while SOF/DCV showed the least. Abstract : Linked Content This article is linked to Papanikolaou and Papadimitropoulos paper. To view this article visithttps://doi.org/10.1111/apt.14580 .